Validity and reliability of a Chinese language suicide screening questionnaire-observer rating (CL-SSQ-OR) assessment for children/adolescents - Yu, Haiping; Tian, Hongjun; Fang, Tao; Zhang, Qiuyu; Wang, Lina; Ma, Xiaoyan; Li, Ranli; Cheng, Langlang; Zhuo, Chuanjun (Frontiers in Psychiatry, 2023)
Background: A Suicide Screening Questionnaire-Observer Rating (SSQ-OR) has been used to assess risk of suicide among individuals and to help clinicians identify and rescue individuals attempting suicide. To prevent the risk of suicide in China, a Chinese language SSQ-OR (CL-SSQ-OR) needs to be introduced. Objective: To test the validity and reliability of a CL-SSQ-OR. Method: A total of 250 individuals were enrolled in this study. Each completed a CL-SSQ-OR assessment, Patient Health Questionnaire-9, and the Beck Scale for Suicide Ideation. Confirmatory factor analysis (CFA) was adopted to determine structural validity. Spearman correlation coefficients were adopted to determine criterion validity. An internal correlation coefficient (ICC) was used to test inter-consistency and Cronbach’s α coefficient was used to test split-half reliability. Results: CFA was conducted with use of the maximum variance method to evaluate the item results. All of the items received scores > 0.40. In addition, good model fit indices were observed for the two-factor structure RMSEA = 0.046, TLI = 0.965, CFI = 0.977. The items’ factor loading of the CL-SSQ-OR in the first factor ranged from 0.443–0.878. The items’ factor loading of the CL-SSQ-OR in the second factor ranged from 0.400–0.810. The ICC of the total CL-SSQ-OR was 0.855. Cronbach’s α was 0.873. Conclusion: The CL-SSQ-OR described here demonstrates ideal psychometric properties and is found to be a suitable tool for screening Chinese children/adolescents who are at risk of suicide.